Activity centred analysis and design in the evolution of learning networks - Goodyear, Peter; Carvalho, Lucila (Proceedings of the International Conference on Networked Learning, 2016)
This paper provides an overview of, and rationale for, an approach to analysing complex learning networks. The approach involves a strong commitment to providing knowledge which is useful for design and it gives a prime place to the activity of those involved in networked learning. Hence the framework that we are offering is known as “Activity Centred Analysis and Design” or ACAD for short. We have used the ACAD framework in the analysis of 20 or so learning networks. These networks have varied in purpose, scale and complexity and the experience we have gained in trying to understand how these networks function has helped us improve the ACAD framework. This paper shares some of the outcomes of that experience and describes some significant new refinements to how we understand the framework. While the framework is able to deal with a very wide range of learning situations, in this paper we look more closely at some issues which are of particular importance in networked learning. For example, we discuss the distributed nature of design in networked learning – acknowledging the fact that learning networks are almost invariably co-configured by everyone who participates in them, and that this aspect of participation is often explicitly valued and encouraged. We see participation in (re)design as a challenging activity: one that benefits from some structured methods and ways of representing and unpicking the tangles of tasks, activities, tools, places and people.